Pelayanan Birokrasi di Era Reformasi, Bagaimana Seharusnya? - Istianda, Meita; ', Darmanto (Jurnal Ilmu Administrasi Negara, 2009)
Public service provided by government has not satisfied society needs because bureau-cracy culture is still influenced by feudalism values. That values enrich corruption practices, collu-sion and nepotism at bureaucracy organization. Indonesia recently has come into reform era markedwith the appearance of new spirit to render governance management based on the Good Gover-nance principles. Government renders that principles by the preparation of Public Service Billdraft, formation of Ombudsman’s Commission , and e_government practices In order to publicservice more efficient and effective, preventing from abuse of power and authority, breaking law,and profligate manner, therefore government staff shall refer on the ethical code for governmentstaff. This article discusses the problems engaged with bureaucracy culture, bureaucracy perfor-mance, e_government, and Good Governance.